2018
DOI: 10.1115/1.4039413
|View full text |Cite
|
Sign up to set email alerts
|

Investigations Into the Flow Behavior in a Nonparallel Shrouded Diffuser of a Centrifugal Fan for Augmented Performance

Abstract: It is a well-known fact that the diffuser of a centrifugal fan plays a vital role in the energy transformation leading to better static pressure rise and efficiency. Many researchers have worked on modified geometry with respect to both impeller and diffuser so as to extract better efficiency of the fan. This paper highlights a unique numerical study on the performance of a centrifugal fan, which has a diffuser having nonparallel shrouds. The shroud geometry is parametrically varied by adopting various converg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the cylindrical coordinate of reference, the well-benchmarked CFD algorithm for moving mesh zones is used to solve the conservation differential equations for continuity, momentum, and scalar transport [18,19]. The numerical analysis's boundary conditions closely match those in the author's relevant experimental data [16].…”
Section: Numerical Model Boundary Conditionsmentioning
confidence: 99%
“…In the cylindrical coordinate of reference, the well-benchmarked CFD algorithm for moving mesh zones is used to solve the conservation differential equations for continuity, momentum, and scalar transport [18,19]. The numerical analysis's boundary conditions closely match those in the author's relevant experimental data [16].…”
Section: Numerical Model Boundary Conditionsmentioning
confidence: 99%
“…He also found that the deriving power of the compressor was decreased due to reduction in the impeller losses. Madhwesh et al [9] examined the effects of splitter vanes at various geometrical locations on the impeller blade. They found that the splitter vanes located near the leading edge improved the static pressure recovery of the fan.…”
Section: Introductionmentioning
confidence: 99%
“…However, diffuser vanes are very distorted and difficult to design, lacking mature theories and experiences. Meanwhile, it is a well-known fact that the diffuser of a centrifugal pump plays a vital role in the energy transformation leading to better pump head and efficiency [2]. Thus, it is significant and necessary to explore an optimal structural configuration of a space diffuser for an improved performance.…”
Section: Introductionmentioning
confidence: 99%